A literary history of medicine : the 'Uyūn al-anbā' fī ṭabaqāt al-aṭibbā' of Ibn Abī Uṣaybi'ah - Savage-Smith, Emilie; Swain, Simon; Gelder, G. J. H. van; Sánchez Rojo, Ignacio Javier (Handbook of oriental studies, 2020)
"A Literary History of Medicine by the Syrian physician Ibn Abī Uṣaybi'ah (d. 1270) is the earliest comprehensive history of medicine. It contains biographies of over 432 physicians, ranging from the ancient Greeks to the author's contemporaries, describing their training and practice, often as court physicians, and listing their medical works; all this interlaced with poems and anecdotes. These volumes present the first complete and annotated translation along with a new edition of the Arabic text showing the stages in which the author composed the work. Introductory essays provide important background. The reader will find on these pages an Islamic society that worked closely with Christians and Jews, deeply committed to advancing knowledge and applying it to health and wellbeing. Contributors: Ignacio Sánchez, N. Peter Joosse, Alasdair Watson, Bruce Inksetter, Franak Hilloowala"--
Keywords: Ibn Abī Uṣaybiʿah, Aḥmad ibn al-Qāsim, : -1269 or 1270; fyysikot; lääketiede; historia; arabimaat; Physicians : Arab countries : Biography; Physicians : Biography; Medicine, Arab; Medicine, Medieval; Medicine, Greek and Roman; Medicine : History; lääketieteen historia